Brief Report: Cesarean Delivery and Subsequent Fecundability. Issue 6 (November 2016) - Radin, Rose G.; Mikkelsen, Ellen M.; Rothman, Kenneth J.; Hatch, Elizabeth E.; Sorensen, Henrik T.; Riis, Anders H.; Kuohung, Wendy; Wise, Lauren A.
Abstract : Background: Studies have shown that cesarean delivery is associated with fewer subsequent births relative to vaginal delivery, but it is unclear whether confounding by pregnancy intention or indication for surgery explained these results. We evaluated the association between cesarean delivery and subsequent fecundability among 910 primiparous women after singleton live birth. Methods: In a cohort of Danish women planning pregnancy (2007–2012), obstetrical history was obtained via registry linkage; time-to-pregnancy and covariate data were collected via questionnaire. Fecundability ratios (FRs) and 95% confidence intervals (CIs) were adjusted for potential confounders. Results: Relative to spontaneous vaginal delivery, emergency cesarean delivery with cephalic presentation showed little association with fecundability (FR = 1.0, 95% CI = 0.83, 1.3), but cesarean delivery with breech presentation (FR = 0.72, 95% CI = 0.53, 0.97) and planned cesarean delivery with cephalic presentation (FR = 0.51, 95% CI = 0.25, 1.0) were associated with reduced fecundability. Conclusions: The cesarean–fecundability association varied by previous fetal presentation and emergency status. Abstract : Supplemental Digital Content is available in the text.